The role of social support in moderating the relationship between HIV centrality, internalised stigma and psychological distress for people living with HIV. Issue 7 (2nd July 2020) - Brener, Loren; Broady, Timothy; Cama, Elena; Hopwood, Max; de Wit, John B.F.; Treloar, Carla
ABSTRACT: Research has documented the negative impact of stigma on health outcomes for people living with HIV (PLHIV). How central HIV is to the identity of the individual may increase the negative effects of stigma, including greater psychological distress, while having strong social supports may play a buffering role. This study aimed to establish whether internalised stigma mediates the relationship between the centrality of HIV identity and psychological distress, while also assessing the role of social support as a moderator. PLHIV ( n = 181) responded to a survey assessing experiences of living with HIV focussed on centrality of HIV identity, internalised stigma, and wellbeing. After controlling for age and education, findings from the mediation analysis show that the more central HIV is to an individual's identity, the more stigma is internalised and the greater the negative impact on psychological wellbeing. However, this is only the case for people with low levels of social support. Regardless of how central HIV is to identity, social support appears to act as a buffer and promote positive wellbeing. For those working with PLHIV, promoting the importance of good social support systems may be one way to address some of the negative impacts of stigma.